Pengaruh Budaya Organisasi dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior Pada Perawat Rawat Inap Gedung Utama RSUD Arifin Achmad Pekanbaru - Siregar, Afifah Salwa; Kasmiruddin, Kasmiruddin (Ekonomis: Journal of Economics and Business, 2024)
The purpose of this research is to find out how organizational commitment and culture influence organizational citizenship behavior (OCB). OCB behavior is the dependent variable (Y), while organizational culture and organizational commitment are the independent variables (X). the research process is quantitative descriptive. Data sources are based on secondary data based on observations made in the research environment and primary data based on questionnaires. The sample for this study consisted of 46 civil servant nurses. The research results found that commitment and organizational culture have a big impact on organizational citizenship behavior.